Metaheuristic Algorithms for Optimization of Varying Efficiency Production Systems - Rudek, Radosław (Algorytmy metaheurystyczne w optymalizacji systemów produkcyjnych o zmiennej efektywności, 2010)
In this paper, we analyse a schedule management problem in production systems with varying efficiency caused by the learning effect. The measurable result of learning is that the time required to produce a single item decreases as more units are produced. First, we provide a short historical review on the discussed issue and present different approaches to model the learning effect in the scheduling context. Since the considered problem seems to be NP-hard, we design and implement fast heuristics and metaheuristic algorithms which are based on simulated annealing, tabu search and genetic algorithms. Numerical evaluation of their efficiency is provided.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 147, s. 232-243
Keywords: scheduling; learning effect; heuristic